Assessment of 51 Progenies of Melia azedarach Linn. - a Promising Agroforestry Tree - Luna, R. K.; Singh, Bikram; Sharma, S. K. (Indian Forester, 2006)
Melia azedarach is a promising agro-forestry tree. Assessment of 9-months old progeny trial of this species consisting of 51 progenies from Punjab, Haryana and Uttaranchal established at Kharkan; Hoshiarpur, Punjab was done. In terms of height and diameter growth progeny No. 14 (Takni, Hoshiarpur) performed the best. Results of analysis of variance for height, diameter at breast height, diameter at ground level, crown diameter, clear bole formation and d2h were highly significant at 1% level of probability. Highest variance (89.75%) was found in d2h whereas the minimum in height trait (20.50%). The heritability estimate for height was the highest (0.44 Â± 0.086) followed by d2h, dbh, diameter at ground level and clear bole formation. Contribution of environmental conditions was found higher than the genetic factors. Phenotypic and genotypic coefficients of variation point out that height and diameter traits can be relied upon for early selection for tree improvement in this species. Cluster analysis revealed that progeny No. 14 and 46 were distantly apart. Principal Component Analysis (PCA) showed that PC-I captured 77.8% of the total variance of which diameter and height exhibited the highest. Based on the results of growth performance and cluster analysis progeny No. 14 proved the best performer. The other 10 promising progenies are ranked on the basis of PCA.